Ankylosing Spondylitis and the Risk of Lung Cancer: A Meta-Analysis and Mendelian Randomization - Ao, Yiyuan; Wen, Yaokai; Li, Yutian; Peng, Haoxin; Wu, Xiangrong; Wang, Zhufeng; Jiang, Yu; Lin, Yuechun; Li, Shuben (Frontiers in Genetics, 2022)
Background It remains uncertain whether ankylosing spondylitis is associated with an increased risk of lung cancer. Methods We conducted a meta-analysis to comprehensively evaluate the correlation between ankylosing spondylitis and lung cancer based on existing literatures. Eligible studies were identified by searching the PubMed, Web of Science, EMBASE, and Cochrane Library before March 26, 2021. Subgroup analyses based on regions were also carried out. To further explore their causality, a two-sample Mendelian randomization analysis was performed, with 23 ankylosing spondylitis-related single nucleotide polymorphisms derived from the largest sample genome-wide association study of ankylosing spondylitis (ebi-a-GCST005529, 22,647 individuals). The inverse variance-weighted method was applied to estimate the causality and the pleiotropy was assessed utilizing the Mendelian randomization-Egger regression approach. Results The meta-analysis including seven studies, with a total of 39,186 individuals, suggested no significant association between ankylosing spondylitis and lung cancer (relative risk, 1.10; 95% confidence interval, 0.89-1.36; I2, 61.8%). After excluding one study leading to high heterogeneity, we found that ankylosing spondylitis was associated with a 19% increased risk of lung cancer (relative risk, 1.19; 95% confidence interval, 1.01-1.40; I2, 0.0%). Subgroup analyses suggested that ankylosing spondylitis was not associated with increased risks of lung cancer in neither European (relative risk, 1.05; 95% confidence interval, 0.80-1.39; I2, 0.0%) nor non-European (relative risk, 1.14; 95% confidence interval, 0.84-1.55; I2, 79.6%) patients. Nevertheless, the Mendelian randomization results indicated that genetically determined ankylosing spondylitis was causally correlated with a remarkably increased risk of lung cancer among European populations (odds ratio, 1.26; 95% confidence interval, 1.07-1.47). Subgroup analyses further elucidated that genetically determined ankylosing spondylitis was causally associated with a notably higher risk of only squamous cell lung cancer (odds ratio, 1.39; 95% confidence interval, 1.05-1.83), rather than lung adenocarcinoma (odds ratio, 1.18; 95% confidence interval, 0.91-1.54). Besides, the results indicated the absence of pleiotropy. Conclusion The results of both modified meta-analysis and mendelian randomization analysis suggested that ankylosing spondylitis was likely to be correlated with the development of lung cancer. Further research is warranted to clarify the specific mechanism regarding the causality between the two diseases.